Jameson and Literature The Novel, History, and Contemporary Reading Practices - Cogle, Jarrad; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2020)
This book demonstrates how Fredric Jameson$1 (Bs understanding of the novel form has heavily influenced his work as a critical theorist. It contends that Jameson$1 (Bs idiosyncratic engagements with the literary canon have had a major impact on his theoretical frameworks, particularly in his sense of historical change. The book investigates Jameson$1 (Bs predominant literary interests in chapters focusing on realism, modernism, postmodernism and genre fiction. These readings provide fresh perspectives on Jameson$1 (Bs career, ones that look beyond his most famous contributions to cultural theory and interpretive practice. Through this work, the book also rethinks the criticism that has surrounded Jameson, while suggesting ways in which his literary interpretation remains useful for contemporary reading practices.s
1. Chapter 1: Historical Contradictions: The Career, Critical Reception, and Reading Practice of Fredric Jameson. - 2.Chapter 2: Jameson and Nineteenth-Century Realism: Generic Boundaries, Historical Transformation, and Affect Theory -- 3. Chapter 3: Jameson and the High Modernist Novel: Absence, Imperialism, and Metacommentaries -- 4. Chapter 4: Jameson and Post-War Literature: Postmodernism, Utopia, and the Collective. - 5. Chapter 5: Conclusion - Jameson, the Novel, and Contemporary Reading Practices.
Keywords: Literature$1 (BPhilosophy.s; Culture$1 (BStudy and teaching.s; Critical theory; Postmodernism (Literature).; Literary Theory; Cultural Theory; Critical Theory; Postmodern Literature